Effect of hypochlorite cleaning on the physiochemical characteristics of polyvinylidene fluoride membranes - Wang, Pan; Wang, Zhiwei; Wu, Zhichao; Zhou, Qi; Yang, Dianhai (Chemical engineering journal (Lausanne, Switzerland : 1996), 2010)
Traditionally, the chemical cleaning is unanimously considered to be an effective means to restore membrane permeability. However, the chemical solutions can also be responsible for changes in membrane properties and thus affect the life-span of membranes. The aim of this study was to gain a better understanding of the effect of sodium hypochlorite cleaning solutions on the changes of physiochemical characteristics of microfiltration (MF) flat sheet membranes made from polyvinylidene fluoride (PVDF). A pilot-scale MBR was operated for 63 d and frequent and high dose sodium hypochlorite cleaning was carried out. The properties of the original and cleaned membranes were compared by pure water flux evaluation, contact angle measurement, mechanical testing, and attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra analysis. Effective removal of the foulant from the membrane surface resulted in more severe fouling. The pure water flux decayed faster with the extension of operation time and the membrane became more and more hydrophilic. The deterioration of ultimate tensile strength and the improvement of the ultimate elongation of membranes showed that membrane became more weak and flexible after hypochlorite cleaning. The results of ATR-FTIR indicated that the sodium hypochlorite cleaning had no vital damage to the chemical structure of PVDF membrane, but exerted impacts on its surface properties.